Quantitative analysis of the labia minora morphology in 400 Chinese women: A new method for assessing the shape of the labia minora - Che, Kexin; Wang, Keke; Yuan, Ye; Li, Fengyong; Li, Qiang (Frontiers in Surgery, 2023)
Purpose To investigate the shape of labia minora in Chinese adult women. Methods Women who visited the Genital Plastic Surgery Center from January 2021 to February 2022 were included and the vulvar regions were photographed. The shape of the labia minora was converted into quantifiable values [left side line segment 1 to 9 (L1 to L9 values) and right side line segment 1 to 9 (R1 to R9 values)]. The 400 enrolled patients were grouped by age, parity, and the types of vulvar surgeries they planned to undergo. Results After a graphic-to-digital and digital-to-graphic conversion, the simulated average image of the labia minora in Chinese adult women was constructed based on the mean values of L1 to L9 and R1 to R9. Comparing the values of Ln and Rn in the four age groups revealed that the mean values of Ln and Rn gradually decreased with age, but only two subgroups showed statistically significant differences (P-value < 0.05). When the patients were stratified according to the number of births and whether labiaplasty was planned to perform, there were no significant differences among all groups (P-value>0.05). Conclusions To measure and evaluate the labia minora, a new assessing method was used. It is an innovative attempt to transform the simple rough description of the shape of the labia minora into more precise data reflecting the shape features. It allows the comparison of labia minora shape between individuals by comparing quantifiable values. Besides, the average shape of labia minora in Chinese adult women was provided visually. Factors including age, parity, and whether the patient planned to undergo labiaplasty were not significantly associated with the shape of the labia minora.